Metabolic instruction of the graft-versus-leukemia immunity - Burk, Ann-Cathrin; Apostolova, Petya (Frontiers in Immunology, 2024)
Allogeneic hematopoietic cell transplantation (allo-HCT) is frequently performed to cure hematological malignancies, such as acute myeloid leukemia (AML), through the graft-versus-leukemia (GVL) effect. In this immunological process, donor immune cells eliminate residual cancer cells in the patient and exert tumor control through immunosurveillance. However, GVL failure and subsequent leukemia relapse are frequent and associated with a dismal prognosis. A better understanding of the mechanisms underlying AML immune evasion is essential for developing novel therapeutic strategies to boost the GVL effect. Cellular metabolism has emerged as an essential regulator of survival and cell fate for both cancer and immune cells. Leukemia and T cells utilize specific metabolic programs, including the orchestrated use of glucose, amino acids, and fatty acids, to support their growth and function. Besides regulating cell-intrinsic processes, metabolism shapes the extracellular environment and plays an important role in cell-cell communication. This review focuses on recent advances in the understanding of how metabolism might affect the anti-leukemia immune response. First, we provide a general overview of the mechanisms of immune escape after allo-HCT and an introduction to leukemia and T cell metabolism. Further, we discuss how leukemia and myeloid cell metabolism contribute to an altered microenvironment that impairs T cell function. Next, we review the literature linking metabolic processes in AML cells with their inhibitory checkpoint ligand expression. Finally, we focus on recent findings concerning the role of systemic metabolism in sustained GVL efficacy. While the majority of evidence in the field still stems from basic and preclinical studies, we discuss translational findings and propose further avenues for bridging the gap between bench and bedside.